Approaches to STI Prevention and Control in a Highly Decentralized State: An Integrative Review - Gómez Castellá, Javier; Díaz Franco, Asunción; Polo Rodríguez, Rosa; del Amo Valero, Julia (Frontiers in Reproductive Health, 2022)
The Spanish health system is highly decentralized and Autonomous Regions (AR) are responsible for managing and implementing the National Strategic Plan for Prevention and Control of HIV and other Sexually Transmitted Infections (STI) (2013–2020) via autonomous plans adapted to the characteristics of each region. The aim of this study is to report on actions taken to specifically address STI prevention and control in the autonomous plans within the mainframe of the National Strategic Plan. An integrative review was performed to analyse the health plans and HIV/STI plans of the Spanish AR during the period of validity of the current National Strategic Plan; 2013–2020. Plans were selected attending to specificity and whether strategies were in force during the year 2020. Our gatherings show that plans are largely focused to HIV prevention and control and, to a lesser extent, to STI prevention. The analysis on pre-existing resources for care of STI varied by region, and epidemiological surveillance systems for STI notification were not completely adopted by all of them. Particularly noteworthy are information campaigns, pre- and post-exposure prophylaxis for HIV, and prevention activities in community settings. The remarkable lack of studies concerning STI resources and investment in Spain highlights the necessity of consensus-based tools for evaluation and future planning of STI prevention and control measures. The high degree of heterogeneity among plans for prevention of HIV infection and STIs also points out a high number of different areas for improvement in the development of new AR plans in HIV/STI.